Effectiveness of Digital Marketing and Product Innovation on Marketing Performance with Competitive Advantage as an Intervening Variable in Small Industries - Rita Setyaningsih; Nur Novia Wati; Rika Marlina; Yusuf (Indonesian Journal of Business Analytics, 2024)
This research aims to improve the marketing performance of rattan SMEs to create advantages for small industries and is expected to be useful for the Cirebon district government so that it can develop the small industrial economy. This type of research uses quantitative descriptive methods and the population in this research is 1,200 people. The type of sample used was 220 people taken as samples using the Slovin formula. This research obtained research instrument method data using questionnaires, then the data was processed using Smart-PLS3. The results of this research show that digital marketing has a positive effect on competitive advantage because value 0.000 < 0.5 digital marketing has a positive effect on marketing performance 3.09 > than 1.96. Competitive advantage has a positive effect on marketing performance because table is 14.305 > 1.96.